Infants' statistical word segmentation in an artificial language is linked to both parental speech input and reported production abilities. Issue 4 (22nd February 2019) - Hoareau, Mélanie; Yeung, H. Henny; Nazzi, Thierry
Abstract: Individual variability in infant's language processing is partly explained by environmental factors, like the quantity of parental speech input, as well as by infant‐specific factors, like speech production. Here, we explore how these factors affect infant word segmentation. We used an artificial language to ensure that only statistical regularities (like transitional probabilities between syllables) could cue word boundaries, and then asked how the quantity of parental speech input and infants' babbling repertoire predict infants' abilities to use these statistical cues. We replicated prior reports showing that 8‐month‐old infants use statistical cues to segment words, with a preference for part‐words over words (a novelty effect). Crucially, 8‐month‐olds with larger novelty effects had received more speech input at 4 months and had greater production abilities at 8 months. These findings establish for the first time that the ability to extract statistical information from speech correlates with individual factors in infancy, like early speech experience and language production. Implications of these findings for understanding individual variability in early language acquisition are discussed. Abstract : Our findings establish for the first time that the ability to extract statistical information from speech correlates with individual factors in infancy, like early speech input and language production.